Tradisi Mekotek Tinjauan Sosiologis Tradisi Penolak Bala dari Desa Adat Munggu Kecamatan Mengwi Kabupaten Badung Bali - Tinangon, Juan Andrew; Punia, I Nengah; Tamim, Imron Hadi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 4 No 1 (2024): JISSOROT, 2024)
This research focuses on the Mekotek tradition, which is a tradition of repelling evil which has deep spiritual and sociological meaning and is traditionally held every 6 months on Saturday Kliwon Kuningan, right on the Kuningan holiday. The aim of this research is to explain and analyze the form and meaning of symbols in the Mekotek tradition. This research uses a research method with a qualitative descriptive approach. The theory that is the analytical tool in this research is Roland Barthes' semiotics with the concept of Two Orders of Signification. The results of this research suggest that the main form of symbols in the Mekotek tradition is the denotational meaning in a symbol in the form of tamiang Kolam, spears, Munggu Kingdom war banners, pulai wood and its ornaments, Bleganjur or gongs, kulkul and clothing. The connotative meaning of the main symbols in the Mekotek tradition represents a means of self-defense, identity as a banner of war and solidarity, respect for ancestors, spiritual, religious dimensions and traditional identity in carrying out the Mekotek tradition. The main symbols in the Mekotek tradition are expressed as elements that have deep mythical meaning such as sacredness and holiness, elements of courage and honor, ancestral strength, aesthetic dimensions, as well as a form of maintaining cultural identity. The Mekotek tradition reflects the local wisdom of the Munggu Traditional Village community which makes it a tradition to repel evil. Bearing in mind that the Mekotek tradition is mandatory for the Munggu Traditional Village community, the implementation of this tradition should not just be a form of ritual, but requires a deep understanding and meaning from a spiritual and sociological perspective of every symbol and action in the Mekotek tradition. Keywords : Mekotek, Semiotic, Mekotek Tradition Symbols, Meaning of Mekotek Tradition, Repelling Evil